2016
DOI: 10.3390/jcm5090080
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vascular Endothelial Growth Factor Concentration and Alveolar Nitric Oxide as Potential Predictors of Disease Progression and Mortality in Idiopathic Pulmonary Fibrosis

Abstract: Background: Declining lung function signifies disease progression in idiopathic pulmonary fibrosis (IPF). Vascular endothelial growth factor (VEGF) concentration is associated with declining lung function in 6 and 12-month studies. Alveolar nitric oxide concentration (CANO) is increased in patients with IPF, however its significance is unclear. This study investigated whether baseline plasma VEGF concentration and CANO are associated with disease progression or mortality in IPF. Methods: 27 IPF patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…An alternative role for C alv NO may be in disease monitoring. Kotecha et al [68] suggested that C alv NO levels were reflective of deteriorating lung function. This is consistent with other studies suggesting that C alv NO levels are inversely related to lung function parameters in fibrotic ILD, a phenomenon not seen with FeNO [73,81,83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative role for C alv NO may be in disease monitoring. Kotecha et al [68] suggested that C alv NO levels were reflective of deteriorating lung function. This is consistent with other studies suggesting that C alv NO levels are inversely related to lung function parameters in fibrotic ILD, a phenomenon not seen with FeNO [73,81,83].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies compared breath biomarkers in IPF patients receiving treatment. Kotecha et al [68], found no difference in C alv NO levels in IPF patients receiving treatment with immunosuppression (either corticosteroids alone or in combination with azathioprine) and untreated patients. Corradi et al [59] found that there was no treatment effect on the presence of…”
Section: Do Levels Of Breath Biomarkers In the Ipf Population Differ Between Treated And Untreated Patients?mentioning
confidence: 94%
See 1 more Smart Citation
“…Concerning the association with pulmonary functional parameters, an inverse correlation between CaNO values and FVC and DLCO has been repeatedly observed, suggesting a potential value of this biomarker in the monitoring of disease progression [ 8 , 40 , 42 , 44 , 45 ]. One study also reported a significant correlation of CaNO with Composite Physiological Index (CPI), further supporting its potential as a severity biomarker in this setting [ 46 ].…”
Section: Extended Feno Analysis In Ilds: Current Evidencementioning
confidence: 99%
“…One study also reported a significant correlation of CaNO with Composite Physiological Index (CPI), further supporting its potential as a severity biomarker in this setting [ 46 ]. Only two studies have specifically investigated the prognostic value of extended FeNO analysis in IPF, reporting a significantly worse survival and functional disease progression in patients with more elevated CaNO values [ 44 , 45 ]. No data are currently available regarding the dynamics of eNO parameters through the follow-up of IPF patients.…”
Section: Extended Feno Analysis In Ilds: Current Evidencementioning
confidence: 99%